The Challenges Faced by Public Primary Schools in Managing School-Based Income-Generating Projects in Bukoba District, Tanzania - Dickson Zephrine; Consolata Chua; Edgar Nderego (East African Journal of Arts and Social Sciences, 2026)
School-based income-generating projects (IGPs) have become an important strategy for public primary schools in Tanzania to supplement government funding and improve the availability of resources for teaching and learning. However, many schools continue to experience challenges in planning, managing, and sustaining these projects, limiting their contribution to school development. This study investigates the challenges faced by public primary schools in managing school-based income-generating projects in Bukoba District. Specifically, the study seeks to identify the key management challenges, examine the factors contributing to these challenges, assess their effects on school operations, and propose practical strategies for improving the management and sustainability of income-generating projects. The study is guided by the pragmatic research paradigm, which supports the use of both quantitative and qualitative approaches to gain a broader understanding of the research problem. A convergent parallel mixed-methods research design is employed, allowing both types of data to be collected simultaneously, analysed separately, and merged during interpretation. The sample size is determined using Yamane's (1967) formula. The study involves 280 ordinary teachers, selected through simple random sampling, while head teachers are selected purposively because of their roles and experience in managing school-based income-generating projects. A structured questionnaire is used as the main instrument for collecting quantitative data from teachers, while semi-structured interviews are conducted with education administrators to obtain deeper insights into the challenges experienced. Quantitative data are analysed using the Statistical Package for the Social Sciences (SPSS) through descriptive statistics and inferential statistics, including Chi-square tests and multiple regression analysis. Qualitative data are analysed using thematic analysis. The findings are expected to provide practical recommendations for policymakers, education authorities, and school leaders to strengthen the management and long-term sustainability of school-based income-generating projects in public primary schools in Tanzania.